Announcement Effects of Open Market Repurchases in China—From Perspective of Enterprise Life Cycle - Xue, Tong; Tsao, Xiuzhe (Journal of Global Economy, Business and Finance, 2024)
This article explores the influencing factors of announcement effects of open market repurchases in China from the perspective of the enterprise life cycle. The findings reveal that the announcement effect of share repurchase is much lower for companies in growth stage than for companies in the maturity and decline stages, confirming the validity of the "free cash flow hypothesis" in the Chinese stock market. Furthermore, the motives of the repurchase and the proportion of shares to be repurchased are crucial elements influencing the announcement effect, which varies depending on the stage of the company's life cycle.